“Si j’avais un salon”/ “If I had a salon”… With Others or on One’s Own ? The Ambivalences of George Sand - Hovelaque, Clémence; Zanone, Damien (Thélème. Revista Complutense de Estudios Franceses, 2026)
George Sand is in literature a “recognised exception”, to use Balzac’s expression, in that she is the only woman to rank among men in the mythology of Romanticism. This formula suggests a tension between the individual and the group that has been successfully overcome: however, it deserves to be questioned. She readily extols the group in her writings, as it reflects her aspiration for fraternity among the arts and the artists, but shows ambivalence toward the groups she might associate with, torn between affiliation and detachment, anxious to preserve her independence. This article proposes to study this ambivalence by establishing a typology of the groups in which Sand participates, before examining the chronology of her relationship with groups throughout her writing career. This journey, which will consider how she represents them in her work, will allow us to follow the evolution of Sand’s conception of the group.